Analisis Hukum Terhadap Tindak Pidana Bully dan Pencegahannya Dilingkungan SDN 22 Lumban Suhisuhi Kecamatan Pangururan Samosir - Hutabalian, Maslon (DOKTRINA: JOURNAL OF LAW, 2024)
Current technological developments not only have a positive impact on society, but often have a negative impact and even have a worse impact, especially among elementary school children. One of the effects of technological progress that can have a negative impact on elementary school students is the use of gejets and the like which are free from control from parents, especially from the school, this can provide opportunities for children at the elementary school level to misuse them. something simple that is easy to pay attention to is giving or sending messages, comments containing ridicule and bullying via WhatsApp, Facebook, etc. without any limits. In the elementary school environment, it tends to occur and is most often found in acts called bullying, both between fellow students and from teachers to students, so that this actually does not need to happen to elementary school children and can be avoided by taking preventive measures from an early age. The urgency of this research was carried out to determine the legal analysis of criminal acts of bullying and their prevention, which aims to ensure that students at elementary school level, especially SD No. 22 Lumban Suhi-Suhi, do not experience bullying and can make prevention efforts.